Role of Injection Depo Medoroxy Progesterone Acetate in the Management of Abnormal Uterine Bleeding in Norplant User (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: This prospective study was undertaken to determine the role of Depomedroxy progesterone acetate (DMPA) in the management of abnormal uterine bleeding associated with norplant use.Methods: The study was carried out in the Department of Family Planning Model Clinic of Sir Salimullah Medical College and Mitford Hospital, Dhaka between June, 2003 to December, 2005. A total 54 clients were consecutively selected, based on predefined enrolment criteria.Results: Over two-thirds (70.6%) of the patients were multipara (2-3 live births), 22% primipara and the rest 7.4% grand-multipara (4 or more live births). Among 54 cases, 45(84%) responded to treatment. Of the 9 (16%) cases who failed to respond to DMPA treatment, 4 cases were given 2nd dose of DMPA. Three cases dropped out after failing the 1st dose and 2 cases refused to receive 2nd dose and their norplant was removed on request. Abnormal per vaginal (P/V) bleeding began from the 1st month of insertion of Norplant with 15 (27.7%) cases in the 1st month, 7(12%) cases between 2nd to 5th months, 16(28%) cases between 6-12 months, 11(20%) between 13-24 months and 5 (9.3%) cases between 25-36 months.Conclusion: The study showed that DMPA is a simple and effective modality of treatment for women with abnormal or irregular uterine bleeding associated with norplant implant use. With increased compliance from clients’ perspective, it could be a good option for treatment of women with abnormal or irregular uterine bleeding caused by norplant implant.Ibrahim Card Med J 2017; 7 (1&2): 80-83